1990
DOI: 10.1002/j.1460-2075.1990.tb07887.x
|View full text |Cite
|
Sign up to set email alerts
|

The tyrosine phosphorylated carboxyterminus of the EGF receptor is a binding site for GAP and PLC-gamma.

Abstract: Phospholipase C‐gamma (PLC‐gamma) and GTPase activating protein (GAP) are substrates of EGF, PDGF and other growth factor receptors. Since either PLC‐gamma or GAP also bind to the activated receptors it was suggested that their SH2 domains are mediating this association. We attempted to delineate the specific region of the EGF receptor that is responsible for the binding, utilizing EGF receptor mutants, PLC‐gamma, and a bacterially expressed TRP E fusion protein containing the SH2 domains of GAP. As previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
187
1
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(204 citation statements)
references
References 39 publications
14
187
1
2
Order By: Relevance
“…Third, recombinant GST-Nck-SH2 and GST-GAP-SH2 fusion proteins were unable to precipitate GAP or Nck, respectively, from the EGF-stimulated cells. Since both Nck and GAP have previously been shown to associated with the activated EGFR (Anderson et al, 1990;Li et al, 1992;Margolis et al, 1990), the data from our experiments implied that Nck and GAP may not even associate stoichiometrically with the same EGFR. Otherwise, Nck and GAP would be in the same complex with activated EGFR and co-immunoprecipitable by using anti-Nck or anti-GAP antibody.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Third, recombinant GST-Nck-SH2 and GST-GAP-SH2 fusion proteins were unable to precipitate GAP or Nck, respectively, from the EGF-stimulated cells. Since both Nck and GAP have previously been shown to associated with the activated EGFR (Anderson et al, 1990;Li et al, 1992;Margolis et al, 1990), the data from our experiments implied that Nck and GAP may not even associate stoichiometrically with the same EGFR. Otherwise, Nck and GAP would be in the same complex with activated EGFR and co-immunoprecipitable by using anti-Nck or anti-GAP antibody.…”
Section: Discussionmentioning
confidence: 58%
“…Guanine nucleotide exchange factors (GEFs) exchange Ras-bound GDP with GTP, whereas GTPase-activating proteins (GAPs) enhance the Ras intrinsic GTP-hydrolyzing activity, converting the active GTP-bound Ras to its inactive GDP-bound form. In EGF stimulated cells, GAP1 is tyrosine phosphorylated and associated, via its N-terminal SH2 domain, with the activated EGF receptor (Anderson et al, 1990;Margolis et al, 1990). As a result, GAP1 is translocated to the plasma membrane and deactivates Ras (reviewed by Boguski and McCormick).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the two isoforms of PLC␥, PLC␥1 and PLC␥2, are activated by protein tyrosine kinases (2, 3, 9). These enzymes contain Src homology 2 and 3 (SH2 and SH3) domains; the SH2 domains are responsible for the binding of these enzymes to tyrosine autophosphorylation sites on activated receptor protein tyrosine kinases (15). In addition, a variety of extracellular signals induce tyrosine phosphorylation of PLC␥1, a step which is essential for enzyme activation and for stimulation of PtdIns(4,5)P 2 hydrolysis (16).…”
mentioning
confidence: 99%
“…Monoclonal Abl08, a gift from Dr. J. Schlessinger, New York University Medical School and Dr. A. Zilberstein, Rhone Poulenc Rorer. CD63 cells [10] and CD126 cells [11] were a gift from Drs. J. Schlessinger and A. Ulrich and the SH2/SH3-containing PLC-?…”
Section: Methodsmentioning
confidence: 99%
“…NIH3T3/HER 14 cells [12] which express approximately 300,000 native EGFR molecules per cell, NIH3T3/CD63 cells (NIH 3T3 cells expressing approximately 300,000 molecules per cell of an active EGFR mutant lacking 63 amino acids from the C-terminus including the 2 tyrosine autophosphorylation sites Y1148 and Y1173) and NIH3T3/ CD126 cells (which express a truncated EGFR lacking 126 amino acids from the C-terminus including the 4 tyrosine autophosphorylation sites Y1068, Y1086, Y1148 and Y1173) were grown to confluence in Dulbecco modified Eagle's medium -50 mg/ml penicillin -10% fetal calf serum [10,11,13]. Membranes were prepared as described elsewhere [121.…”
Section: 3• Preparation Of Cell Membranesmentioning
confidence: 99%